Engaging in predatory practices: How editors persuade prospective authors - Bocanegra-Valle, Ana (Círculo de Lingüística Aplicada a la Comunicación, 2023)
A number of studies have explored the main features of predatory practices that prevail in predatory academic journals and conferences. However, not much has been investigated regarding the ways predatory journal editors convey credibility and trustworthiness when addressing scholars looking for publication outlets and, more specifically, what interpersonal resources (like proximity or engagement markers) are used to persuade them. This exploratory study draws on a dataset of fifty email messages from predatory publishers collected during the past two years. It seeks to delve into the ways predatory journal editors address “scholar customers” with the aim of persuading them to submit their work. This dataset was first coded following Hyland’s models of proximity and interaction in academic texts, and then qualitatively analysed using NVivo 11 Pro. The analysis shows that (i) textual data provide direct evidence of the texts that predatory publishers send to scholars and the interpersonal dialogue they intend to build with authors in haste for publication; (ii) interactional resources abound, particularly engagement markers, which explicitly aim at building a rapport with the prospective author; and (iii) these predatory texts also contain other engagement-related elements directed to have an effect on the reader’s decision for eventual submission.